2023
DOI: 10.3390/polym15030616
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shear on the Properties of an Associated Polymer Solution for Oil Displacement

Abstract: Polymer flooding is one of the techniques used to enhance oil recovery from depleted hydrocarbon reservoirs. Although this technology is popular for this application, the shearing effect in the injection process causes poor performance, which is an obstacle to meeting the needs of the formation. An experimental evaluation of the rheological properties, viscoelasticity, hydrodynamic size, static adsorption, and seepage characteristics of the associated polymer solution before and after shearing was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This enhances the shear tolerance of polymer solutions, and changes in rheological parameters and viscoelastic behavior do not impart a significant loss. 89 Both laboratory and simulation results have revealed the increase in oil recovery efficiency for hybrid formulation, as compared to conventional water or polymer flooding. On the basis of Figure 7, greater oil recovery was the outcome of improved rheology and stability.…”
Section: Methods Of Enhancing Stability Of Nanofluid Dispersionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhances the shear tolerance of polymer solutions, and changes in rheological parameters and viscoelastic behavior do not impart a significant loss. 89 Both laboratory and simulation results have revealed the increase in oil recovery efficiency for hybrid formulation, as compared to conventional water or polymer flooding. On the basis of Figure 7, greater oil recovery was the outcome of improved rheology and stability.…”
Section: Methods Of Enhancing Stability Of Nanofluid Dispersionsmentioning
confidence: 99%
“…It has been shown that some polymers, such as associative polymers, can interact through hydrophobic associations to restore a significant amount of their solution properties after shear is applied. This enhances the shear tolerance of polymer solutions, and changes in rheological parameters and viscoelastic behavior do not impart a significant loss . Both laboratory and simulation results have revealed the increase in oil recovery efficiency for hybrid formulation, as compared to conventional water or polymer flooding.…”
Section: Influence Of Chemical Structures In Fluid–fluid and Fluid–ro...mentioning
confidence: 96%
“…Polymer flooding was an important and extensively used technique for improving oil recovery in the mid-later period of oilfield development. [1][2][3][4][5][6] However, there are still many challenges in practical applications, such as reduced long-term stability at high-temperature and in high-salinity brines, as well as limited propagation in low-permeability rocks. 7 Especially, the most widely used partially hydrolyzed polyacrylamide (HPAM) 8,9 with the advantages of simple synthesis, controllable molecular weight, and improved water flooding development efficiency still had poor shear-resistance, temperature and salt resistance, suffering viscosity loss in the presence of reservoir brines and elevated temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer flooding was an important and extensively used technique for improving oil recovery in the mid‐later period of oilfield development 1–6 . However, there are still many challenges in practical applications, such as reduced long‐term stability at high‐temperature and in high‐salinity brines, as well as limited propagation in low‐permeability rocks 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobically associated polyacrylamides have potential applications in various elds such as drug delivery, nanomaterial synthesis, water treatment, and the petrochemical industry owing to their molecular structures and properties [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%